Retirement and decline in episodic memory: analysis from a prospective study of adults in England. (6th July 2019) - Romero Starke, Karla; Seidler, Andreas; Hegewald, Janice; Klimova, Anna; Palmer, Katie
Abstract: Background: Work has been associated with cognitive health. We examined whether retirement from work is associated with a decrease in episodic memory and whether this effect differs when considering workers' occupational class. Methods: In this prospective study using the English Longitudinal Study of Ageing (ELSA), we examined 1629 persons aged 50–75 years who were in paid work at baseline. A two-slope random effects linear regression centred at retirement was used to study the effect of retirement on episodic memory. The potential effect modification by occupational class was examined. Results: While memory trajectories show slightly decreasing memory scores before and afterretirement, the decreasing rates for both periods were similar [episodic memory β2b −β2a = −0.03, 95% confidence interval (CI) −0.08, 0.02]. When stratifying by occupational class, there was also no substantial difference in episodic memory trajectories before and after retirement. However, the lower occupational class showed a clear decline in episodic memory with time (pre-retirement β2a = −0.11, 95% CI −0.19, −0.03; post-retirement β2b = −0.13, 95% CI −0.19, −0.07) which was not evident for the higher occupational classes. Conclusions: Our results show no observable difference in trajectories of change in episodic memory before and after retirement. However, the steeper memory decline in workers belonging to the lower occupational class may limit their prospect of prolonging their working lives. Hence enrichment programmes for the prevention of memory decline for these workers should be considered.